The Impact of Blended Learning Models on Arab EFL Learners - Barkaoui, Mohamed Elboussairi Salih Elhaj Mohamed (Indonesian Journal of Learning Education and Counseling, 2025)
This review examines the impact of blended learning models (BLMs), particularly flipped classrooms and online assignments, on Arab students learning English as a Foreign Language (EFL). It explores how these approaches influence motivation, engagement, and language proficiency within the unique educational and cultural context of the Arab world. The study employs a content analysis methodology, systematically analyzing empirical studies from reputable academic databases to identify key themes, patterns, and trends related to the effectiveness of BLMs. Through coding and thematic categorization, the analysis provides a structured understanding of how these models shape EFL learning outcomes. Theoretical foundations such as constructivism and connectivism underpin the study, emphasizing active learner engagement and digital access in the learning process. While BLMs offer benefits such as improved language skills and increased learner autonomy, challenges related to technological accessibility and cultural relevance persist. The review underscores the need for further research to refine and optimize BLM strategies for Arab EFL learners, focusing on overcoming barriers and adapting content to local educational needs